2005
DOI: 10.1021/jp0467604
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Excitation Spectroscopy of Silver Nanoparticle Arrays

Abstract: Frequency-scanned excitation profiles of coherent second harmonic generation (SHG) were measured for silver nanoparticle arrays prepared by nanosphere lithography. The frequency of the fundamental beam did not coincide with the localized surface plasmon resonance (LSPR) of the nanoparticles and was tuned so that the coherent second harmonic (SH) emission was in the region of the LSPR at 720−750 nm. The SH emission from the arrays was compared with a smooth silver film to identify an enhancement of SH emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 61 publications
5
80
0
Order By: Relevance
“…Silver triangular nanoprisms of different sizes (edge length) were prepared using a two-step seed mediated procedure as reported recently [11,[23][24][25]. Solution (40 ml) containing AgNO 3 (2.9 Â 10 À4 M) and trisodium citrate (2.5 Â 10 À4 M) was cooled in an ice-bath.…”
Section: Material Synthesis and Characterizationmentioning
confidence: 99%
“…Silver triangular nanoprisms of different sizes (edge length) were prepared using a two-step seed mediated procedure as reported recently [11,[23][24][25]. Solution (40 ml) containing AgNO 3 (2.9 Â 10 À4 M) and trisodium citrate (2.5 Â 10 À4 M) was cooled in an ice-bath.…”
Section: Material Synthesis and Characterizationmentioning
confidence: 99%
“…[1][2][3][4][5] Copper properties such as high conductivity, photosensitivity, and low cost makes it a promising material for chemical, electronic, and photonic integration in miniaturized devices for use in biological nanosensors, [6][7][8][9][10] as well as its capability of insertion in host polymer matrices for nonlinear optical applications. [11][12][13] Optical properties such as extinction and plasmon resonance are highly size dependent below 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…11 Enhancements as large as 10 7 have been reported in nanoparticle clusters, enabling, for example, Raman spectroscopy of single molecules. 12,13 Other than Raman spectroscopy, [14][15][16] this phenomenon has found applications in optical third-harmonic generation, [17][18][19] as well as in second-harmonic generation, [20][21][22][23][24][25][26] which is the subject of this paper. Nahata et al 23 demonstrated an ∼10 4 -fold increase in the efficiency of optical second-harmonic generation from concentric silver ring structures centered around a 200-nm aperture (bull's-eye structure) compared to a silver film with an unadorned aperture.…”
mentioning
confidence: 99%
“…Podlipensky et al 24 observed second harmonic generation (SHG) enhancement from ellipsoidal silver nanoparticles in a glass matrix grown by means of Ag + -Na + ion exchange. More recently, Moran et al 25 have demonstrated second harmonic excitation spectroscopy of silver nanoparticle arrays, which were fabricated by nanosphere lithography. In that work, a weak out-of-plane LSPR mode was made to overlap with the second harmonic of the incident laser, so that the resulting SHG emission signal became proportional to the plasmon * To whom correspondence should be addressed.…”
mentioning
confidence: 99%